PEMBUATAN PETA SITUASI SKALA 1:500 SEBAGIAN DUSUN SIDOMULYO DESA BANYURIPAN dan DESA BELUK KECAMATAN BAYAT KABUPATEN KLATEN PROVINSI JAWA TENGAH - , NICKY AGSEN H ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final assignment consists of five chapters on measuring and land mapping activities. The activities are Fieldwork Practice to create information embodies in situation map. The map consists of spatial data with planimetric and high point details. The steps of the measurement are map control frame making which consists of horizontal and vertical control frame measurement, planimetric and high point detail measurement, and also the digital and layout description. The result is information embodied in situation map which provides earth surface spatial data of partial Sidomulyo village, Banyuripan village, and Beluk village Bayat District, Klaten Regency, Jawa Tengah province with 1: 500 scale. The measurement is in UTM (Universal Transverse Mercator) projection system and divided into 4 index map.